Trauma-related infections due to cluster munitions - Youssef Fares; Mohamad El-Zaatari; Jawad Fares; Nora Bedrosian; Nadine Yared (Journal of Infection and Public Health, 2013)
Trauma-related infections remain a concerning and potentially avoidable complication of conflict-related injuries. During the Israeli conflict in South Lebanon, more than four million sub-munitions were dropped over South Lebanese soil. In this study, we will explore the different types of infection caused by sub-munitions and penetrating agents. This prospective study took place from 2006 to 2012 at the Lebanese University within the Faculty of Medical Sciences’ departments. This study sample consisted of 350 injured casualties. Patients suffered from blast injuries with fragmentations targeting the head, face, torso, abdomen, pelvis and extremities. Of the 350 causalities studied, 326 (93.1%) were males, and 24 (6.9%) were females. Ages varied between 10 and 70 years, with the average age being 27 years. Of the 350 patients studied, 68 (19.4%) developed infections. Infections varied between pseudomonas, Escherichia coli, Candida and fungus and sometimes led to necrosis. Vaccinations, antibiotic therapies and proper wound irrigation must be performed at appropriate emergency units. Excision and complete debridement of necrotic and contaminated tissue should also be performed. The Convention on Cluster Munitions of 2008 should be adhered to, as these weapons indiscriminately and disproportionately harm civilians, thereby violating the well-established international principles governing conflict. Keywords: Cluster bombs, Cluster munitions, Trauma, Infection, Lebanon